A boost for performance or a sense of corporate social responsibility? A bibliometric analysis on sustainability reporting and firm performance research (2000-2022) - George Nyantakyi; Francis Atta Sarpong; Philip Adu Sarfo; Nneka Uchenwoke Ogochukwu; Winnifred Coleman (Cogent Business & Management, 2023)
Recently, there has been a growing concern regarding the impact of businesses on the environment and society and the pursuit of profit maximization. The current scenario has led to increased attention toward ESG disclosure and sustainability reporting and their probable impact on the performance of firms. Consequently, ESG disclosure and sustainability reporting have emerged as captivating subjects within corporate governance literature. Through a comprehensive review, this study aims to explore the current trends and patterns in sustainability reporting and ESG disclosure and their effects on firm performance. A dataset spanning 23 years (2000 to 2022) was compiled to conduct this analysis, comprising 656 scholarly publications obtained from the Web of Science. Utilizing the VOSViewer software, various bibliometric analyses were performed, including co-authorship, citation, cartography, and bibliographic coupling. The study's findings indicate an average annual publication growth rate of 50.43% since 2010. However, despite this publication volume increase, most studies were conducted in developed countries like Italy, England, the USA, and China. The results of the keyword cluster analysis highlight sustainability and sustainability reporting as prominent research themes. In contrast, keywords like greenwashing and climate change were found to be less prevalent. Regarding the focus of the studies, the majority concentrated on analyzing the nexus between ESG disclosure, sustainability reporting, and firm performance regarding firm value and leverage, with a sizeable proportion exploring the impact of board diversity and gender diversity. The study also established a low link between sustainability reporting and firm performance.
Keywords: 650; ESG disclosure; Sustainability reporting; firm performance; bibliometric analysis; Vosviewer